H is for hawk - Macdonald, Helen, 1970- (New York : Grove Press, 2014)
Recounts how the author, an experienced falconer grieving the sudden death of her father, endeavored to train for the first time a dangerous goshawk predator as part of her personal recovery.
Includes bibliographical references (pages 285-297).
Keywords: Macdonald, Helen, -- 1970-; Macdonald, Helen, -- 1970-; Goshawk; Grief; Falconry; Spirituality; Goshawks; Bereavement; Falconry